School Staff Perceptions of Military-Connected Students in Civilian Public Schools: Implications for Teachers, Counselors, and School Staff. (3rd April 2017) - Capp, Gordon; Astor, Ron Avi; Benbenishty, Rami; Weiss, Eugenia; Pineda, Diana
ABSTRACT: Nearly all public school districts serve some of the 4 million military-connected students in the United States. Little is known about the perceptions of school staff and their understanding of the challenges facing these students in their schools. Results from 4, 616 California school staff in 2011 and 2013 indicate that many believe in their capacity to respond to the needs of these students. However, in many cases, they do not know whether particular challenges or assets exist. These results emphasize the importance of efforts to highlight the needs of this population and that school staff are integral sources of support.